2017
DOI: 10.3390/en10040464
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Logistics in Practical Levelized Cost of Energy Reduction Implementation and Government Sponsored Cost Reduction Studies: Day and Night in Offshore Wind Operations and Maintenance Logistics

Abstract: This paper reveals that logistics make up at least 17% of annual operational expenditure costs for offshore wind farms. Annual operational expenditure is found to vary by a factor of 9.5, making its share of levelized cost of energy for offshore wind range from 13% to 57%. These are key findings of a 20-month research project targeting cost reduction initiatives for offshore wind systems. The findings reveal that cost-out measures are difficult to implement due to cultural differences. Implementation efforts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…The cost of Operation and Maintenance (O&M) of wind power plants is having a significant effect on the levelized cost of energy (LCOE). () A key challenge in O&M management is achieving a reliable prediction of mechanical failures. This could enable a better understanding of deterioration mechanisms and provide benefits by allowing a sufficient lead time for making decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of Operation and Maintenance (O&M) of wind power plants is having a significant effect on the levelized cost of energy (LCOE). () A key challenge in O&M management is achieving a reliable prediction of mechanical failures. This could enable a better understanding of deterioration mechanisms and provide benefits by allowing a sufficient lead time for making decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The trends clearly indicate that offshore wind farms (OWFs) occupying a larger area, with wind turbines of higher rated power, located in deeper waters, and at larger distances to shore, will be favoured (Rodrigues et al, 2015). Due to their significant contribution to the operational expenditures (OpEx) and to the overall cost of energy, operation and maintenance (O&M) of the devices will play a pivotal role in determining the profitability of a project (Poulsen et al, 2017). For this reason, flexible and comprehensive tools are needed to grasp the complex dynamics of the OWF and provide support in the choice and dispatch of the O&M assets.…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, the Wind Energy Institute estimated service and spare parts costs as 26% of the variable costs for German turbines operation and maintenance costs [15]. More recently, [16] indicated that the relative OPEX share of total levelized costs of energy may vary from 13% to 57% over the life-cycle of an offshore wind farm. This adds another important aspect to the analysis of operation and maintenance costs, i.e., its wide variation between different cases and situations.…”
Section: Introductionmentioning
confidence: 99%